The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1186/s12873-015-0044-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of injury and associated factors among patients visiting the Emergency Departments of Amhara Regional State Referral Hospitals, Ethiopia: a cross-sectional study

Abstract: BackgroundInjury significantly affecting the health and well-being of the society.The prevalence tends to be higher in low income countries. The aim of this study was to assess the prevalence of injury and associated factors among patients visiting emergency departments of Amhara Regional State referral hospitals.MethodsInstitution based cross sectional study was conducted from March to April 2014. The systematic random sampling technique was employed to select the study participants. The data were collected u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
32
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 11 publications
7
32
7
Order By: Relevance
“…But it was higher than studies conducted University of Gondar (25%) 7 and Tikur Anbesa Hospital (32%) 22 and this discrepancy might be due to poor road safety, more motorcycle transportation in our study area. It was lower than a study conducted in Amhara regional State (55.6%) 6 and Jimma University Referral Hospital 5 and this is explained by study setting and large sources of population compared to this study area. The prevalence of injury in one of Nigerian Tertiary Hospital was lower than half of ours and this might be due to better mode of transportation and road safety 23 .…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…But it was higher than studies conducted University of Gondar (25%) 7 and Tikur Anbesa Hospital (32%) 22 and this discrepancy might be due to poor road safety, more motorcycle transportation in our study area. It was lower than a study conducted in Amhara regional State (55.6%) 6 and Jimma University Referral Hospital 5 and this is explained by study setting and large sources of population compared to this study area. The prevalence of injury in one of Nigerian Tertiary Hospital was lower than half of ours and this might be due to better mode of transportation and road safety 23 .…”
Section: Discussioncontrasting
confidence: 72%
“…The commonest mechanism of injury was Assault (49.9%) and road traffic accidents (48%) 7 . Another multicenter study conducted in Amhara regional state showed that the prevalence of injury in the region was 55.5% 6 . Those who are young and daily laborers, substance abusers and those who are with low monthly incomes were the most likely injury victims 6 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Ethiopia there is high report of injuries from health facilities (6,7). However, health facilities reports did not show how many cases of injuries were work places related and could not well address what factors were associated with those injuries and illness (7,8). There are also few fragmented empirical studies on predictors or determinants of occupational injury and illness (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Although disasters are manageable and preventable they are still considered as a major public health issues. In Ethiopia, currently traumatic injuries especially road tra c accidents are major issues (7).…”
Section: Introductionmentioning
confidence: 99%